If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-4=2(x+1)+3x
We move all terms to the left:
5x-4-(2(x+1)+3x)=0
We calculate terms in parentheses: -(2(x+1)+3x), so:We get rid of parentheses
2(x+1)+3x
We add all the numbers together, and all the variables
3x+2(x+1)
We multiply parentheses
3x+2x+2
We add all the numbers together, and all the variables
5x+2
Back to the equation:
-(5x+2)
5x-5x-2-4=0
We add all the numbers together, and all the variables
-6!=0
There is no solution for this equation
| 17=12x-9x+12x+2 | | -2=9+y | | 3a(2)^2+1=5a(2) | | 4n+15=8n+1 | | 72=5u | | 14=6y-4y | | −12=9x+15−6x | | x/4-3=22 | | 2m=–4+m | | 4-x+3=3x-5 | | 1x+1/3=3x+1 | | 1+2x=-x+13 | | 11x-(9x-5)=23 | | 5x+21=26 | | 3-y÷9=1 | | 2(x-9)+x-2=-50 | | X(x+1)+x=62 | | 121/2=2w+2(31/2 | | z/9+9=−61 | | -3x+1=-15 | | 3/10(x+20)=12 | | 4x+8=-64-2x | | 15+250x=10+275x | | -6x-4=3x-31 | | z9+9=−61 | | -12=n+7-5 | | 24y+4=16y-28 | | 3x+6x+7=-38 | | 42=-30+4.95r | | x–112=–7 | | b=-3-5= | | (2)/(x)+3=(3)/(2x)+(19)/(6) |